Childhood onset of narcolepsy-cataplexy syndrome in Turkey: clinical and genetic study - Pelin, Zerrin; Bozluolcay, Melda; Kaynak, Derya; Kaynak, Hakan (The Turkish Journal of Pediatrics, 2002)
Narcolepsy is a disabling sleep disorder characterized by excessive daytime sleepiness and abnormal manifestations of rapid eye movement (REM) sleep including cataplexy, sleep paralysis and hypnagogic hallucinations. It is known to be complex disorder in which both genetic predisposition and environmental factors play a role. In humans, susceptibility to narcolepsy is tightly associated with a specific HLA allele, DQB1*0602. In this report, we took advantage of the ongoing genetic study in Turkish narcoleptic patients to document clinical and genetic data of eight patients whose onset of symptoms were in the childhood period.